Development of Extended-Release Mini-Tablets Containing Metoprolol Supported by Design of Experiments and Physiologically Based Biopharmaceutics Modeling - Michele Georges Issa; Natalia Vieira de Souza; Bruna Wenyi Chuang Jou; Marcelo Dutra Duque; Humberto Gomes Ferraz (MDPI AG, 2022)
The development of extended-release dosage forms with adequate drug release is a challenge for pharmaceutical companies, mainly when the drug presents high solubility, as in Biopharmaceutics Classification System (BCS) class I. This study aimed to develop extended-release mini-tablets containing metoprolol succinate (MS), while integrating design of experiments (DOE) and physiologically based biopharmaceutics modeling (PBBM), to predict its absorption and to run virtual bioequivalence (VBE) studies in both fasted and fed states. Core mini-tablet formulations (F1, F2, and F3) were prepared by direct compression and coated using nine coating formulations planned using DOE, while varying the percentages of the controlled-release and the pore-forming polymers. The coated mini-tablets were submitted to a dissolution test; additional formulations were prepared that were optimized by simulating the dissolution profiles, and the best one was submitted to VBE studies using GastroPlus® software. An optimized formulation (FO) containing a mixture of immediate and extended-release mini-tablets showed to be bioequivalent to the reference drug product containing MS when running VBE studies in both fasted and fed states. The integration of DOE and PBBM showed to be an interesting approach in the development of extended-release mini-tablet formulation containing MS, and can be used to rationalize the development of dosage forms.